2014
DOI: 10.1098/rsif.2014.0158
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic constants enable the emergence of bistability in dual phosphorylation

Abstract: Dual phosphorylation of proteins is a principal component of intracellular signalling. Bistability is considered an important property of such systems and its origin is not yet completely understood. Theoretical studies have established parameter values for multistationarity and bistability for many types of proteins. However, up to now no formal criterion linking multistationarity and bistability to the parameter values characterizing dual phosphorylation has been established. Deciding whether an unclassified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(133 citation statements)
references
References 24 publications
2
131
0
Order By: Relevance
“…In the absence of an inhibitor, the double phosphorylation motif Eq (1) can possess either a single or two stable steady states of the doubly-phosphorylated form of the substrate C PP , [50, 54, 58, 59]. Therefore in our study we consider two cases: first, when the motif Eq (1) is monostable and second, when this motif is bi-stable.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of an inhibitor, the double phosphorylation motif Eq (1) can possess either a single or two stable steady states of the doubly-phosphorylated form of the substrate C PP , [50, 54, 58, 59]. Therefore in our study we consider two cases: first, when the motif Eq (1) is monostable and second, when this motif is bi-stable.…”
Section: Resultsmentioning
confidence: 99%
“…Note that all potential binding/unbinding constants are fixed at the same nominal value, and, by analogous distributive mechanism, we mean the distributive mechanism with these binding/unbinding constants and the same sets of catalytic constants. A choice of sufficiently different catalytic constants in phosphorylation can result in bistability in a purely distributive model, as shown in figure 3a (also see [39]). By contrast, the two mixed models exhibit monostable behaviour.…”
Section: Two-site Modificationmentioning
confidence: 99%
“…An interesting and unique twist of this motif is that the bistability resulting from modication of the oligomer extends to the monomer due to intrinsic substrate competition and because both species are in equilibrium with each other. We also demonstrated that kinetic cooperativity of multisite modication systems is not a requirement for bistability if there are multiple enzymes regulating the modication steps and if some can only catalyse a subset of the individual modication steps, resulting eectively in the same kinetic asymmetry[22,23] as kinetic cooperativity. While oligomers might be particularly suited for this mechanism due their symmetrical structure, bistability through multi-enzyme regulation could in principle arise in any mul-tisite PTM system.…”
mentioning
confidence: 85%